Kedudukan dan Fungsi Dewan Pengupahan dalam Rangka Penetapan Upah Minimum Tenaga Kerja di Provinsi Nusa Tenggara Timur - Ignatius Loyola Julio Doni Kuma; Kotan Y. Stefanus; Rafael Rape Tupen (Pusat Riset dan Inovasi Nasional, 2025)
The Wage Council of East Nusa Tenggara Province is a Non-Governmental Institution that is Independent, Self-Reliant, and Tripartite, tasked with recommending the Minimum Wage for Laborers to the Governor of East Nusa Tenggara Province for determination. The determination of the Minimum Wage for laborers in East Nusa Tenggara Province is established based on the Governor's Decree to be implemented by Companies in providing wages for laborers, especially in the Districts/Cities throughout East Nusa Tenggara Province where the Wage Council has not been formed. The Wage Council of East Nusa Tenggara Province as a Non-Structural Institution that is independent and self-reliant, in carrying out its duties and responsibilities, has not been effective when the survey for decent living needs is omitted as regulated in Law Number 13 of 2003 concerning Manpower in conjunction with Government Regulation Number 78 of 2015 concerning Wages. The tasks and responsibilities of the Provincial Wage Council in determining the minimum wage of laborers in East Nusa Tenggara Province are stipulated in Law Number 11 of 2020 concerning Job Creation as a Replacement for Law Number 13 of 2003 which technically eliminates the Decent Living Needs Survey for one (1) person as a benchmark in recommending Minimum Wage Determination to the Governor. The formulation of the problem in this research is: (1) What is the Position and Function of the Wage Council in Determining the Minimum Wage of Laborers in East Nusa Tenggara Province? (2) What are the Prospects of the Wage Council of East Nusa Tenggara Province in the Future? The author conducted normative research supported by empirical research as complementary data. The focus of the research is the Wage Council as a non-governmental, independent, and self-reliant institution that has a position and function in determining the minimum wage since the Decent Living Needs Survey was eliminated and the Prospects of the Provincial Wage Council in the Future. The results of this research indicate that: (1) The Position and Function of the Wage Council as an independent/self-reliant institution in reality are not independent/self-reliant due to the involvement of third parties, namely the Central Bureau of Statistics. (2) The Prospects of the Wage Council in the Future after the Decent Living Needs Survey is abolished.